Modelling the effects of asset management decisions on a railway track section - Prescott, Darren; Andrews, John D. (2014)
This paper reports on the development of a Markov model that uses real-world deterioration, inspection and maintenance data to assess railway track asset management. The model allows both asset management personnel and track maintenance engineers to evaluate the effects of ballast maintenance on the rail network and to predict the track condition as it changes over time given particular maintenance and inspection routines. An example analysis of a railway track section is presented, focussing on the investigation of the effects of varying the inspection interval on the track performance throughout its lifetime. It is demonstrated how the model results can be interpreted to give some indication of the effect of certain asset management decisions on the potential for fines resulting from delays and cancellations or safety risk relating to operating trains on a degraded track.